Effects of Low-Frequency Repetitive Transcranial Magnetic Stimulation of the Bilateral Parietal Cortex in Patients With Tourette Syndrome - Fu, Mengmeng (Front Neurol, 2021)
Background: Traditional medical treatments are not effective for some patients with Tourette syndrome (TS). According to the literature, repetitive transcranial magnetic stimulation (rTMS) may be effective for the treatment of TS; however, different targets show different results. Objective: To assess the efficacy and safety of low-frequency rTMS in patients with TS, with the bilateral parietal cortex as the target. Methods: Thirty patients with TS were divided into two groups: active and sham groups. The active group was subjected to 0.5-Hz rTMS at 90% of resting motor threshold (RMT) with 1,200 stimuli/day/side, whereas the sham group was subjected to 0.5-Hz rTMS at 10% of RMT with 1,200 stimuli/day/side with changes in the coil direction. Both groups were bilaterally stimulated over the parietal cortex (P3 and P4 electrode sites) for 10 consecutive days. The symptoms of tics and premonitory urges were evaluated using the Yale Global Tic Severity Scale (YGTSS), Modified Scoring Method for the Rush Video-based Tic Rating Scale (MRVBTS), and Premonitory Urge for Tics Scale (PUTS) scores at baseline, the end of the 10-day treatment, 1 week after treatment, and 1 month after treatment. Results: At the end of the 10-day treatment, the YGTSS total, YGTSS motor tic, YGTSS phonic tic, MRVBTS, and PUTS scores in the active group significantly improved and improvements were maintained for at least 1 month. Conclusions: Low-frequency bilateral rTMS of the parietal cortex can markedly alleviate motor tics, phonic tics, and premonitory urges in patients with TS.